May Measurement Month 2018: an analysis of blood pressure screening results from United Arab Emirates. (28th August 2020) - Yusufali, Afzalhussein; Bazargani, Nooshin; Bin Belaila, Buthaina A; Suhail, Aisha M; Shuri, Hassan H; Agrawal, Amrish; Muhammed, Khalifa; Gabroun, Ahmed; Albawab, Amer; Vazir, Zainab; Ravi Kumar, Rajakumari; Ghannam, Dana; et al.
Abstract: Hypertension is one of the most important modifiable risk factors for cardiovascular disease and death even in high-income countries. According to the PURE Study, globally only half of hypertensives are aware and less than a fifth controlled. May Measurement Month (MMM) is a global campaign to raise awareness and screen for high blood pressure (BP) in lieu of formal screening. United Arab Emirates (UAE) has taken part in MMM since its inception and here data from MMM18 are reported. Trained volunteers from 54 sites screened 31 316 individuals from all the Emirates of UAE using convenience sampling. Blood pressure measurement, the definition of hypertension, and statistical analysis followed the standard MMM protocol. The mean age was 36.8 ± 11.4 years and 18 411(59%) were male. Participants of Arab descent were 11 829 (38%) and 11 569 (37%) were South Asian. Mean body mass index was 26.8 ± 5.29 kg/m 2 . Of those screened, 7 917 (25%) had never had a BP recorded, while 16 892 (54%) had recorded BP in the previous year. After imputation, 6 243 (20%) had hypertension. Of those participants, only 2 540 (41%) were aware and 2 331 (37%) were on antihypertensive medication, of which 61% were controlled. Of all hypertensives, only 23% were controlled. May Measurement Month in UAE expanded significantly compared to 2017. A quarter had never had BP measured and awareness of hypertension low (41%). This opportunistic screening method found a substantial number of adults with untreated or inadequately treated hypertension.